CHARACTERISTICS OF THE KALLIKREIN-KININ SYSTEM IN PATIENTS WITH GLOSSALGIA - E.N. Dychko; P.L. Sribnik; A.V. Schtompel (Ukrainian Medical Stomatological Academy, 2016)
The paresthetica's pain maxillofacial have enough ubiquitous disease and includes glossodiniyu, glossalgia, neuralgia, neuritis and causalgia, what may constitute together 2-3% of dental patients. There are most interested neurologists, psychiatrists and neuro-dentists, which often refer patients for medical assistance in the study of the nature of this phenomenon. Experts tend to believe that the mechanism of pain is dominated by vascular disorders of the structural or functional nature, mainly, in the microvasculature, causing the tissue ischemia, the imbalance of tissue hormones, the failure of metabolic processes, the accumulation of acid radicals, the excessive irritation of sensory pain receptors of the nociceptive substances. However, the value of biologically active substances tissue stills not be examined, especially to ensure the tone of preand capillary vessels and forming the main chain links of the pathogenesis of pain paresthetica's maxillofacial region, that will facilitate the development of therapeutic and preventive correction with the higher effect. Therefore, we examined the 37 individuals suffering from the parestetica's pain in the mouth, one to three years, but were treated the general practice dentists unsuccessfully. Among the patients were women aged from 42 to 62 years, they had underlying chronic diseases of the nervous, digestive and cardiovascular systems. Clinical signs glossalgia were typical of both subjective and objective plan. The control group consisted of 35 healthy subjects. The status of the kallikrein-kinin system was determined in 5 ml. fresh blood by level prekallikrein (PK), spontaneous esterase activity (SEA) and the level of kallikrein inhibitor (IC) according to known methods R.W. Colman et al. (1969). The studies found out the vast number of patients glossalgia and noted elevated blood pressure both in large, medium and small sized blood vessels and, especially, in the covering of the site that localized the paresthetica's algic sensations. The structural disorders predominantly cerebral blood vessels in the internal carotid artery were less defined. Obviously, hypertension, vascular tone phenomena arise due to an imbalance of tissue hormones that regulate the vascular tonic properties. Previously, we found that patients with glossalgia takes place excessive stress in the catecholamine system, that is accompanied by excessive production of tissue adrenaline and his predecessors. It can be assumed that it's counterbalance has signs of weakening both the level of activity in the form of hormones cholinergic and kinin systems and the result of this provokes are the chemia in the cover tissues(GPRS) and skin. The hypoxia and excessive formation of oxidized form of the acid radical products are the potent nociceptive stimuli, sensory devices. This is confirmed by the level and activity of hormones kinin system. So, the glossalgia reduce the levels of the hormone kallikrein precursor prekallikrein significantly, as well as, the spontaneous esterase activity with a significant increase in the level of kallikrein inhibitor. The imbalance of the tissue biogenic amines towards the activation of the adrenal system modifies the tonic properties of blood vessels, especially in the microvasculature and in the direction of vasospasm. This is one of the main links in the chain of pathogenesis of pain phenomenon that must be taken into account in the preparation of therapeutic and preventive action of glossalgia.